2010
DOI: 10.5042/tldr.2010.0166
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics and prevention of body shape distortion

Abstract: Biomechanics and prevention of body shape distortion Feature Patterns of body shape distortion Changes in body shape could be considered to have become synonymous with individuals described as having complex health care needs. Irrespective of diagnosis, any individual developing a destructive habitual lying posture can be considered at risk of developing distortions of body shape which will compromise respiration, circulation and digestion. These habitual postures can develop because of movement difficulties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Whilst this review has presented some small scale evidence regarding postural care interventions, of particular importance is the lack of evidence regarding NTPE and 24‐hr postural care service provision. It has been suggested that effective 24‐hr postural care can prevent deformity (Crawford & Stinson, ; Hill & Goldsmith, ) and thus avoid the negative health and quality of life implications associated with poor posture and avoid invasive interventions such as surgery for scoliosis (Waugh & Hill, ) which is frequently associated with major complications (Beckmann et al., ). The lack of research evidence to support the efficacy of NTPE and 24‐hr postural care needs to be addressed urgently, including a focus on the specific issues that may arise in relation to interventions involving people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst this review has presented some small scale evidence regarding postural care interventions, of particular importance is the lack of evidence regarding NTPE and 24‐hr postural care service provision. It has been suggested that effective 24‐hr postural care can prevent deformity (Crawford & Stinson, ; Hill & Goldsmith, ) and thus avoid the negative health and quality of life implications associated with poor posture and avoid invasive interventions such as surgery for scoliosis (Waugh & Hill, ) which is frequently associated with major complications (Beckmann et al., ). The lack of research evidence to support the efficacy of NTPE and 24‐hr postural care needs to be addressed urgently, including a focus on the specific issues that may arise in relation to interventions involving people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, postural care (the term adopted in this review to include all the individual components of a postural management programme outlined above) has been defined as a way of preserving and re‐establishing body shape for people with movement difficulties (RCGP, ). The biomechanics of body shape distortion and the use of therapeutic positioning to prevent body shape distortion have recently been summarized (Hill & Goldsmith, ). Validated indices to measure symmetry have also been developed (Goldsmith, Golding, Garstang, & MacRae, ) which increase sensitivity to the early signs of asymmetry, and indicate the therapeutic positioning needed to protect and restore body shape (Goldsmith & Goldsmith, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gibson & Frank ; Frank et al . ), and possibly worsened by the distorting effects of gravity on body shape (Hill & Goldsmith ).…”
Section: Introductionmentioning
confidence: 99%
“…The discomfort increases across time, and may be associated with one or more factors such as instability, sliding, excessive heat build-up, stiffness, excessive localized soreness or pain, spasticity, or stretch. It may be specific in location or generalized (Geyer et al 2003;Gibson & Frank 2005;Frank et al 2012), and possibly worsened by the distorting effects of gravity on body shape (Hill & Goldsmith 2010).…”
Section: Introductionmentioning
confidence: 99%